Entanglement Classification For Three-qubit Pure Quantum System Using Special Linear Group Under The Slocc Protocol - Amirul Asyraf Zhahir; Mohd Ilias M Shuhud; Bahari Idrus; Hishamuddin Zainuddin; Nurhidaya Mohamad Jan; Siti Munirah Mohd; Mohamed Ridza Wahiddin (International Journal of Advanced Computer Science and Applications, 2024)
Indexed by Scopus